Psychosocial aspects of functioning of women in postmenopausal period: a preliminary study - Walczak, Aleksandra; Wiśniewska, Barbara (Menopause Review/Przegląd Menopauzalny, 2012)
Introduction : Women’s functioning in the postmenopausal period is more difficult not only due to somatic symptoms caused by hormonal changes but also due to psychosocial factors. Its multiplicity and the necessity of quick adjustment to the new requirements of every-day life may cause e.g. such psychological effects as anxiety or depression. Aim of the study : to define psychosocial factors determining functioning of postmenopausal women and a correlation with the level of anxiety and depression. Material and methods : The study group included 31 females (47-60) with different chosen psychosocial factors, specified in a designed questionnaire. The patients completed also the Polish adaptation of State-Trait Anxiety Inventory (STAI) and Beck Depres-sion Inventory (BDI) to analyze the correlation of anxiety and depression with psychosocial factors. Results : There is e.g. a correlation between age (p = 0.022; r = –0.411), and satisfaction with relationship (p = 0.038; r = –0.374), occurrence of current emotional problems (p = 0.007; r = 0.475) and a level of anxiety as a state and the correlation between the number of children (p = 0.009; r = –0.461) and labors (p = 0.011; r = –0.448) and the level of anxiety as a feature. The psychosocial factors which correlate significantly with depression were e.g. age (p = 0.037; r = –0.377) and the regularity of gynecological care (p = 0.026; r = 0.4). Conclusions : The results of this study indicate an undoubted influence of chosen psychosocial factors on functioning of women in the postmenopausal period. Because of an increased level of depression in analysed females, not only regular gynecological care but also psychological support is recommended.